2011
DOI: 10.1039/c1cp00011j
|View full text |Cite
|
Sign up to set email alerts
|

W-Band pulse EPR distance measurements in peptides using Gd3+–dipicolinic acid derivatives as spin labels

Abstract: We present high field DEER (double electron-electron resonance) distance measurements using Gd(3+) (S = 7/2) spin labels for probing peptides' conformations in solution. The motivation for using Gd(3+) spin labels as an alternative for the standard nitroxide spin labels is the sensitivity improvement they offer because of their very intense EPR signal at high magnetic fields. Gd(3+) was coordinated by dipicolinic acid derivative (4MMDPA) tags that were covalently attached to two cysteine thiol groups. Cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 51 publications
4
79
0
Order By: Relevance
“…The T 1 value of the Mn 2+ -EDTA-tagged p75DD at 10 K was 150 μs, similar to that found for Gd 3+ -labeled proteins (∼100 μs), 13,26 and the T M value was 6.8 μs ( Figure S3, Supporting Information), that is, similar to the T M of 7.6 μs measured for a Gd…”
Section: 2supporting
confidence: 82%
“…The T 1 value of the Mn 2+ -EDTA-tagged p75DD at 10 K was 150 μs, similar to that found for Gd 3+ -labeled proteins (∼100 μs), 13,26 and the T M value was 6.8 μs ( Figure S3, Supporting Information), that is, similar to the T M of 7.6 μs measured for a Gd…”
Section: 2supporting
confidence: 82%
“…Our investigations made so far could not fully elucidate the reason for the reduction of the modulation depth at prolonged τ 2 delays and further experiments are required. A relaxation driven mechanism appears most plausible, as also suggested by the temperature dependence of this effect [10]. Moreover, we expect this effect to be specific to high-spin Gd(III) ions, as we are not aware of such a reduction effect in distance measurements between nitroxides.…”
Section: Application To Long Distancesmentioning
confidence: 65%
“…Accordingly, prolongation of the observation window results in a reduction of the modulation depth. In a previous study, it has been shown that this reduction mechanism does not only depend on τ 2 , but also on temperature [10]. In order to gain further insight into the origin of this effect, we studied the dependence on τ 2 of both λ 2P and the echo signal V 0 /V ref at various concentrations.…”
Section: Application To Long Distancesmentioning
confidence: 94%
See 2 more Smart Citations